Unshared Identity : Posthumous paternity in a contemporary Yoruba community - Ololajulo, Babajide (African humanities series., 2019)
Unshared Identity employs the practice of posthumous paternity in Ilupeju-Ekiti, a Yoruba-speaking community in Nigeria, to explore endogenous African ways of being and meaning-making that are believed to have declined when the Yoruba and other groups constituting present-day Nigeria were preyed upon by European colonialism and Westernisation. However, the author's fieldwork for this book uncovered evidence of the resilience of Africa's endogenous epistemologies. Drawing on a range of disciplines, from anthropology to literature, the author lays bare the hypocrisy underlying the ways in which dominant Western ideals of being and belonging are globalised or proliferated, while those that are unorthodox or non-Western (Yoruba and African in this case) are pathologised, subordinated and perceived as repugnant. At a time when the issues of decolonisation and African epistemologies are topical across the African continent, this book is a timely contribution to the potential revival of those values and practices that make Africans African.